The Three P’s: Parotid, PD-L1, and Pembrolizumab - Amanda Wiggins; Zhaohui Arter; Tamie Kerns (Case Reports in Oncological Medicine)
We present a case of recurrent, platinum-refractory undifferentiated carcinoma of the parotid which was treated with checkpoint inhibitor, Pembrolizumab, and achieved a complete response to therapy. We review the literature of checkpoint inhibitor use in undifferentiated carcinoma of the parotid.